Curriculum Materials, 1974. ASCD Exhibit of Curriculum Materials at Association for Supervision and Curriculum Development Annual Conference. (29th, Anaheim, California, March 1974.) - Association for Supervision and Curriculum Development, Washington, DC.; Association for Supervision and Curriculum Development, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This publication catalogs the materials received for and displayed at the Association conference. Entries are divided into sections on general curriculum development and materials and on the subject areas traditionally found in public schools. Most entries are categorized by level--elementary, middle, or secondary schools. Information is provided concerning the sources and the availability of the material. (MLF)
Availability: Association for Supervision and Curriculum Development, Suite 1100, 1701 K Street, N.W., Washington, D.C. 20006 (Stock Number 611-74014, $2.00, Quantity Discounts).
ERIC Note: A related document is ED 061 637.
Educational level discussed: Kindergarten.
Educational level discussed: Middle Schools.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Career Education; Consumer Education; Curriculum Development; Driver Education; Elementary School Curriculum; Guidance Programs; Instructional Materials; Kindergarten; Mass Media; Middle Schools; Secondary School Curriculum; Special Education; Units of Study; Reference Materials, Bibliographies